Upregulated Connexin 43 Induced by Loss-of-Functional S284L-Mutant α4 Subunit of Nicotinic ACh Receptor Contributes to Pathomechanisms of Autosomal Dominant Sleep-Related Hypermotor Epilepsy - Kouji Fukuyama; Masashi Fukuzawa; Ruri Okubo; Motohiro Okada (Pharmaceuticals, 2020)
To study the pathomechanism and pathophysiology of autosomal dominant sleep-related hypermotor epilepsy (ADSHE), this study determined functional abnormalities of glutamatergic transmission in the thalamocortical motor pathway, from the reticular thalamic nucleus (RTN), motor thalamic nuclei (MoTN) tosecondary motor cortex (M2C) associated with the S286L-mutant α4β2-nicotinic acetylcholine receptor (nAChR) and the connexin43 (Cx43) hemichannel of transgenic rats bearing the rat S286L-mutant Chrna4 gene (S286L-TG), which corresponds to the human S284L-mutant CHRNA4 gene using multiprobe microdialysis, primary cultured astrocytes and a Simple Western system. Expression of Cx43 in the M2C plasma membrane fraction of S286L-TG was upregulated compared with wild-type rats. Subchronic nicotine administration decreased Cx43 expression of wild-type, but did not affect that of S286L-TG; however, zonisamide (ZNS) decreased Cx43 in both wild-type and S286L-TG. Primary cultured astrocytes of wild-type were not affected by subchronic administration of nicotine but was decreased by ZNS. Upregulated Cx43 enhanced glutamatergic transmission during both resting and hyperexcitable stages in S286L-TG. Furthermore, activation of glutamatergic transmission associated with upregulated Cx43 reinforced the prolonged Cx43 hemichannel activation. Subchronic administration of therapeutic-relevant doses of ZNS compensated the upregulation of Cx43 and prolonged reinforced activation of Cx43 hemichannel induced by physiological hyperexcitability during the non-rapid eye movement phase of sleep. The present results support the primary pathomechanisms and secondary pathophysiology of ADSHE seizures of patients with S284L-mutation.